Ensuring Safety in Dental Clinics: A Systematic Review of Infection Control Measures - Alla Eid Alraddadi,; Alhassan Khalid Alsaiari,; Fahd saeed alyami,; Almuhannad Hamdan Salh Alyahiwi,; Mansour Dhaifallah Ahmed Muharraq,; Ahmed Asaad Ahmed Ghazwani,; Saleh Ali Alyami,; Hussam Khaled Albouji, (The Bioscan, 2025)
Infection control in dental clinics is a critical aspect of ensuring patient and staff safety, particularly given the high risk of cross-contamination in these settings. This systematic review examines the effectiveness of various infection control measures implemented in dental clinics, including personal protective equipment (PPE), sterilization protocols, environmental cleaning practices, hand hygiene, and aerosol management. A comprehensive search of peer-reviewed studies published between 2016 and 2025 was conducted, adhering to PRISMA guidelines. The findings highlight best practices and emerging technologies that enhance safety and compliance with global standards. Challenges such as cost, staff training, and adherence to protocols are also discussed, providing actionable recommendations for dental practitioners and policymakers. This review underscores the importance of robust infection control strategies in promoting safer dental environments and mitigating risks associated with infectious diseases.